Pregnancy after kidney transplantation: clinical features, complications and outcomes - E. I. Prokopenko; I. G. Nikolskaya; A. V. Vatazin; F. F. Burumkulova; D. V. Gubina (Вестник трансплантологии и искусственных органов)
Pregnancy after kidney transplantation (KT) has become more common, but the risk of complications and adverse obstetric outcomes in this group of women remains high.Objective: to study pregnancy complications and outcomes in kidney recipients and renal graft (RG) survival after childbirth.Material and methods. The study included 22 pregnancies in 20 women with RG (transplants performed in 2006–2020). The comparison group consisted of 20 healthy women who had 20 pregnancies. Frequency and nature of pregnancy complications, neonatal health indicators, and pregnancy outcomes were evaluated. Graft survival was compared in the main group and in a group of 102 women after KT who did not have pregnancies.Results. Compared with healthy women, RG recipients had a higher rate of preeclampsia (25% and 0%, p = 0.047), fetal growth restriction (30% and 0%, p = 0.020), gestational diabetes (40% and 5%, p = 0.020), asymptomatic bacteriuria (35% and 5%, p = 0.044), preterm birth (60% and 0%, p < 0.001), and cesarean section (70% and 10%, p < 0.001). Median gestational age and birth weight were significantly lower in women with RG: 36.0 [33.9; 37.4] vs. 38.9 [38.9; 39.6] weeks, p < 0.001, and 2405 [2023; 2958] vs. 3355 [3200; 3690] g, p < 0.001, respectively. The rate of favorable pregnancy outcomes after KT was 81.8%, or 90% when early pregnancy loss is excluded. Two children were found to have genetic diseases passed from the mother. Graft survival did not differ between RG recipients with and without pregnancy, p = 0.272.Conclusions. Pregnancy outcomes in patients with RG are generally favorable, pregnancy and childbirth do not affect graft survival. When planning pregnancy after KT, it is necessary to consider the risk of complications and the possibility of transmitting genetic disorders to offspring.